Controlled mesoporous film formation from the deposition of electrosprayed nanoparticles. Issue 6 (3rd June 2017) - Tang, Justin; Gomez, Alessandro
ABSTRACT: Thin films of controlled morphology were fabricated by electrospray drying a colloidal nanoparticle suspension using a conductive and volatile solvent and impacting the nanoparticles on a substrate. Three parameters were used for control: impact velocity, size of the nanoparticles or nanoparticle agglomerates, and solvent volatility. The impact velocity was controlled by charging nanoparticles through electrospray dispersion and varying the electric field driving the particle impaction. It was found that the structure is governed by the relative importance of charged particle drift imposed by the external electric field and the thermal velocity due to Brownian motion. Peclet number correlates with the morphology of the deposit where columnar structures result from high Pe, corresponding to ballistic deposition and porous, fractal-like structures result from small Pe. These patterns match predictions based on Monte Carlo simulations in the literature. For dispersions with higher nanoparticle concentrations, droplet evaporation causes densification of the particle ensemble to form a spherical aggregate that deposits in a predominantly ballistic manner, with smaller aggregates forming denser films. If the droplet evaporation lifetime is altered for the aggregates to be partially wet upon impacting the substrate, the subsequent rapid evaporation of the remaining solvent on the substrate leads to formation of films with high interconnectivity. Films formed by the electrospray technique have large-scale uniformity and their structure is independent of thickness. The interpretation of the observed morphologies in terms of Peclet number and Damkhöler number provides a conceptual framework for a rational design of film structures as required by many applications. Copyright © 2017 American Association for Aerosol Research